Evaluation of Mean Platelet Volume in Diabetes Mellitus and Its Role in Microvascular Complications - Prasad, Sruthi; Prakash, Vibha (Annals of Pathology and Laboratory Medicine, 2018)
BACKGROUND Diabetes mellitus (DM) is a metabolic disorder characterised by hyperglycaemia. The hyperglycaemia results in altered platelet function as reflected in the platelet indices (mean platelet volume-MPV, platelet distribution width and plateletcrit). Altered platelet function has also been implicated in the occurrence of diabetic vascular complications. Evaluation of platelet indices may serve to provide an insight into the pathogenesis of DM as well as possibly evaluate the risk of progression of the disease. The aim of the current study was to evaluate the MPV in patients with DM and compare it with a non-diabetic control group. We also attempted to determine the association between MPV and microvascular complications within the diabetic cohort. METHODS The study was carried out on patients with diabetes mellitus, attending the medicine out-patient department. Relevant history was taken and fasting blood glucose and hematological parameters (platelet indices and complete blood counts) were assessed as a part of the routine investigations requested by the physician itself. A total of 320 diabetics were screened for the study. After applying exclusion criteria, 52 diabetics were included in the study. We also included 62 non-diabetic, age and sex matched controls in the study. Statistical analysis was performed. RESULTS AND CONCLUSION: MPV levels were significantly higher in diabetic patients when compared to non-diabetic controls. Also, within the diabetic group, MPV values were significantly higher in diabetics with microvascular complications (24 patients) as opposed to the ones without. MPV is a simple, convenient and cost-effective routine hematological investigation which plays a significant role in the pathogenesis of diabetes mellitus and may serve as a useful prognostic marker to herald the onset of microvascular complications in the diabetic population.